Discourses of professional identities and linguistic capital formation of international STEM faculty. Issue 52 (July 2021) - Sharma, Bal Krishna; Hussein, Ibtesam
Abstract: This article investigates the discourses of professional identities and linguistic capital formation communicated by international scholars in the STEM disciplines in the US university context. In so doing, the study examines interviews of 17 such individuals and identifies two key discursive processes: the formation of a marketable self and the enactment of the legitimacy of World Englishes. The first discursive process is used by the professionals to position themselves as novice scholars needing to build necessary linguistic capital for employment and communication in the instructional setting. The second version of their discursive positioning, which was formed later in their career, demonstrates a competent self that legitimizes their existing linguistic capital and the ownership of non-Inner Circle Englishes for academic communication. As the participants position their identities vis-à-vis their profession, they claim transformation of the self in defining their linguistic capital and competence across time and space. The findings overall show that the (re-)formation and conversion of international STEM scholars' linguistic capital are variously shaped by relations of power influenced by the linguistic market and their respective disciplinary communities.